Scotch verdict : the real-life story that inspired the children's hour - Faderman, Lillian (Columbia University Press, 2013)
In 1810, a Scottish student named Jane Cumming accused her school mistresses, Jane Pirie and Marianne Woods, of having an affair in the presence of their students. Dame Cumming Gordon, the wealthy and powerful grandmother of the accusing student, advises her friends to remove their daughters from the Drumsheugh boarding school. Within days, the institution is deserted and two women are deprived of their livelihoods. Award-winning author Lillian Faderman recreates the events surrounding this notorious case, which became the basis for Lillian Hellman's famous play, The Children's Hou.